The Effect of Students’ Self-Assessment on Their English Performance in ELT Classroom - Kusrini, Nurul Azizah Ria (Kreasi Teknologi Informasi, 2023)
This study aimed to describe whether the students’ self assessment provides prominent effect on their English performance. This study used library research which was divided into three parts. First part was the concept of Assessment in general and self-assessment in language teaching. The second part discusses both the possible benefit and limitation of the use of students’ self-assessment. The third part discusses validity and the procedure of conducting self-assessment to improve students’ performance in English language teaching. The study shows that self-assessment contributed to student learning and that the effects grow larger with direct instruction on self-assessment procedures.